Comparative Study of Bullying Prevention by High Schools in Sabang City: A Literature Review - cutnovayanti ubbg; rahmattullah; akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This comparative study investigates the approaches and strategies employed by high schools in Sabang City to prevent and address bullying among students. Bullying is a significant issue in educational environments, leading to detrimental effects on students' mental health, academic performance, and overall well-being. This research conducts a literature review, drawing on various academic sources, policy documents, and case studies to analyze the effectiveness of different anti-bullying programs and initiatives implemented in secondary schools. The study aims to identify key factors that contribute to successful bullying prevention efforts and highlight best practices that can be adopted across schools in Sabang City. It examines existing frameworks and methodologies, such as peer support systems, counseling services, and collaborations with parents and community organizations. Furthermore, the research underscores the importance of fostering a supportive school culture that prioritizes respect, inclusivity, and open communication among students and staff. The findings reveal a diverse range of strategies employed by high schools in Sabang City, with particular emphasis on community involvement and the integration of educational curricula that promote empathy and conflict resolution skills. This paper contributes to the broader discourse on bullying prevention in educational settings and offers recommendations for enhancing existing programs to create safer and more supportive environments for all students.